El Excentrico, 1973-05-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
May 20, 1973 [20 de mayo de 1973]. No volume or issue number. Cover has a photograph and reelection advertisement for San Jose councilman David Goglio.